Examining Community of Inquiry Model in Influencing E-Learning Usage among Female Students - Alaa Ibrahim Mahmood Al-Nuaimi (International Review of Management and Marketing, 2017)
This study explores the relationship between online social games and the e-learning usage by investigating the impact of social and cognitive presence on e-learning usage among female students through playing online social games. The use of online social games tools is noticed to be high among female students. Meanwhile, an e-learning environment that has the features of social network tools such as games has great potential to innovate and stimulate the continual usage of E-learning among students, by fostering social interaction and knowledge sharing among the students, especially among female students to be able to facilitate social interaction, since female students are more comfortable sharing ideas among their peers. The findings of this study revealed that, cognitive presence has positive significant impact on E-learning usage. Meanwhile, social presence does not have a significant impact on E-learning usage.